Peningkatan dan Pengembangan Daya Saing bagi Umkm Kripik Salak di Kabupaten Sleman - Dian Retnaningdyah; Reto Ika Sundari; Eko Riswanto; Paryanto Paryanto (Sekolah Tinggi Ilmu Manajemen YKPN Yogyakarta, 2016)
Abstract Today Improving and developing competitiveness for Micro, Small and Medium Enterprises (SMEs) become very important for the development of Indonesian economy. SMEs play an important role in supporting the development of regional economy, which will ultimately have an impact on the national economy. SMEs in Sleman district engaged in the processing zalacca chips, its existence gives a positive value in the economy. Support and attention from stakeholders are very necessary for the sustainability of its business. This programs try to provide an explanation of the importance of the role of human resource innovation capability and technological strategies such as information technology and appropriate technology to support the development and improvement of the competitiveness of SMEs, especially for businessmen of zalacca chips in order to be able to play in the global markets.